Image reconstruction from few views by non-convex optimization - Sidky, E.Y.; Chartrand, R.; Xiaochuan Pan (2007 IEEE Nuclear Science Symposium Conference Record, 2007)
Image reconstruction for fan-beam computed tomography (CT) from projection data containing a small number of views is investigated. An iterative algorithm is developed that seeks to minimize the total p-variation of the reconstructed image subject to the constraint that the estimated projection data agree with the available data to within a specified data tolerance e. A preliminary investigation on the dependence of image quality as a function of p and e is performed.